2018
DOI: 10.1038/s41374-018-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-137 is a tumor suppressor in endometrial cancer and is repressed by DNA hypermethylation

Abstract: Endometrial cancer is the most common gynecological cancer in the United States. We wanted to identify epigenetic aberrations involving microRNAs (miRNAs), whose genes become hypermethylated in endometrial primary tumors. By integrating known miRNA sequences from the miRNA database (miRBase) with DNA methylation data from methyl-CpG-capture sequencing, we identified 111 differentially methylated regions (DMRs) associated with CpG islands (CGIs) and miRNAs. Among them, 22 DMRs related to 29 miRNAs and within 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 42 publications
1
56
2
1
Order By: Relevance
“…Interestingly, our former research con rmed a positive role of miR-137 in LSD1 expression, which was contrary to several studies reporting that miR-137 directly binds to LSD1 [23,26,51,52]. The contradicted outcomes might be associated with the various biological features of different cell types, and we deduced that there probably exist intermediary regulators working between miR-137 and LSD1 during the osteogenesis of hASCs.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, our former research con rmed a positive role of miR-137 in LSD1 expression, which was contrary to several studies reporting that miR-137 directly binds to LSD1 [23,26,51,52]. The contradicted outcomes might be associated with the various biological features of different cell types, and we deduced that there probably exist intermediary regulators working between miR-137 and LSD1 during the osteogenesis of hASCs.…”
Section: Discussioncontrasting
confidence: 99%
“…An understanding of the miRNAs associated with EC initiation and progression is crucial for the development of improved therapeutic techniques. Previous studies have demonstrated that numerous miRNAs are associated with EC (27)(28)(29). In the current study, to the best of our knowledge, expression status, functions and governing molecular mechanisms of miR-873 in EC were detected for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, miR-137 is often downregulated due to hypermethylation of its CpG island 28 . miR-137 hypermethylation leads to its inhibition in many tumors, such as colorectal cancer, pancreatic cancer, and endometrial cancer [29][30][31] . Functional analysis has indicated that miR-137 can inhibit cell proliferation, cell cycle arrest and apoptosis, cell migration and invasion, and affect chemoresistance [32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%